A Content Analysis of CSR Reporting in the Fast Food Industry: The Case of McDonald’s and Yum! Brands - Kuschmierz, Luise (2013)
Purpose - The objective of the research is to critically examine how companies in the fast food industry make use of CSR report communication channels. It raises the question of whether companies in the fast food industry are addressing NGO stakeholder issues in their CSR report as well as whether they seek to legitimise their activities.